KEMALA PERTIWI: EFFORTS TO IMPROVE THE WELFARE OF THE BETUNG BARAT VILLAGE COMMUNITY, ABAB DISTRICT, PENUKAL ABAB LEMATANG ILIR REGENCY, SOUTH SUMATRA THROUGH THE MANAGEMENT OF ORGANIC WASTE - Amalia, Richa; Wahyudi, Hangge Daud (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The waste management practices in Betung Barat Village were previously poorly managed. Waste was merely piled up around homes, in water channels, or burned. These methods have proven to harm the environment, resulting in air pollution. This environmental contamination also negatively impacted public health due to water sources being polluted by waste, contributing to cases of stunting among children in the village. PT Pertamina EP Raja Tempirai implemented the Sustainable Waste Management Group Program in synergy with PHE Raja Tempirai (Kemala Pertiwi) to address this issue. This program aims to integrate waste management with health initiatives, thereby providing economic benefits to the community of Betung Barat Village, Abab District, Penukal Abab Lematang Ilir Regency (PALI), South Sumatra Province. The program involves forming community groups, training sessions, and developing local tourism as part of efforts to empower and improve the community's welfare. The key activities of the Kemala Pertiwi program include maggot cultivation, freshwater fish farming, organic vegetable farming, and preventing stunting by utilizing the produce from these activities as a healthy food source.